Rethinking Arts Appreciation through Jacques Ranciere’s Critical Aesthetics (Asia Pacific Journal of Social Innovation, 2022)
The aim of this article is twofold. First, it attempts to elucidate the conceptual junctions between philosophical aesthetics and politics to appropriate the former in the discussion about the cultural and socio-political realities of a society. Second, it seeks to integrate, especially in the Arts and Appreciation subject, the critical and emancipatory potential of aesthetics in order to transform and make it relevant to society. Using Jacques Ranciere’s critical aesthetics as hermeneutical lens, I argue inthis paper that if Philosophy were to continue to make itself relevant in the Philippine setting it has to permeate into the General Core subject which every Filipino college student has to take. The Art Appreciation subject, in particular, must be infused with a reconfigured understanding of aesthetics in order to depart from the traditional Humanities subject. To avoid repeating the latter under a different name, the descriptions, aims, and contents of Art Appreciation must be recalibrated by grounding it on critical aesthetics that consequently allows it to explore its subtle connection to politics, which will, in turn, provide a fertile ground for analyses and discussions, which can potentially help diagnose and raise consciousness into the socio-cultural and political issues faced by society.